Efektivitas Pendidikan Karakter “CARE” Sebagai Sarana Literasi Pencegahan dan Penanganan Bullying Pada Anak Di Madura - Hera Wahyuni (Journal of Social, Culture, and Language, 2023)
The aim of the research is to determine the effectiveness of "CARE" character education as a literacy tool for preventing and handling bullying in children in Madura. The research was conducted in Madura, especially in Bangkalan Regency, in 2 junior high schools in class VIII (ages 13-15 years). This research model is included in the quantitative research category. The instrument in this research is related to literacy in preventing and handling bullying in junior high school students by implementing CARE character education. Instruments are tools for collecting and processing data about the variables studied. Specifically, all these phenomena are called research variables. In this study, the author used test instruments, namely pretest (before socialization of bullying prevention and handling literacy with "CARE" character education) and posttest (after socialization of bullying prevention and handling literacy with "CARE" character education was carried out). The results of this research show that there was a significant change in the results of the pretest and posttest instrument scores in both schools after the literacy outreach on the prevention and handling of bullying with "CARE" character education was carried out. Keywords: Bullying, Character Education, CARE